Progress of Coupled Heat Transfer Mechanisms of Regenerative Cooling System in a Scramjet - Ni He; Chaoyang Liu; Yu Pan; Jian Liu (Energies, 2023)
The feasibility of regenerative cooling technology in scramjet engines has been verified, while the heat transfer behavior involved in the process needs further study. This paper expounds on the necessity of coupled heat-transfer analysis and summarizes its research progress. The results show that the effect of pyrolysis on heat transfer in the cooling channel depends on the heat flux and coking rate, and the coupling relationship between combustion and heat transfer is closely related to the fuel flow rate. Therefore, we confirm that regulating the cooling channel layout according to the real heat-flux distribution, suppressing coking, and accurately controlling the fuel flow rate can contribute to accomplishing the optimal collaborative design of cooling performance and combustion performance. Finally, a conjugate thermal analysis model can be used to evaluate the performance of various thermal protection systems.